Analisis Rasio Untuk Menilai Kinerja Keuangan Pada PT. Indofood Sukses Makmur Tbk. Periode 2017-2021 - Sulis Mifthaul Nisaa; Muh. Ikhwan Maulana Haeruddin; Anwar Ramli; Romansyah Sahabuddin; Burhanuddin Burhanuddi (Pusat Riset dan Inovasi Nasional, 2023)
This istudy iaims ito ianalyze ithe icompany's ifinancial iperformance iusing ifinancial iratios, iamong iothers, iProfitability iRatios, iSolvency iRatios, iLiquidity iRatios, iand iActivity iRatios iat iPT, iIndofood iSukses iMakmur iTbk. iThose ilisted ion ithe iIndonesia iStock iExchange isamples itaken iwere ithe ifinancial istatements iof iPT. iIndofood iSukses iMakmur iTbk. iPeriod i2017-2021. iThe itype iof idata iused iin ithis iresearch iis iquantitative idata. iThe iresults iof ithis istudy ishow ithat ithe iprofitability iratio ias imeasured iby iReturn ion iassets i(ROA) iand iReturn ion iEquity i(ROE) ifor i2017-2021 iis iquite iefficient. iThe isolvency iratio imeasured iusing ithe iDebt ito iAsset iRatio i(DAR) iand ithe iDebt ito iEquity iRatio i(DER) ifor i2017-2021 iis isaid ito ibe ihealthy. iThe iliquidity iratio ias imeasured iusing ithe iCurrent iRatio i(CR) iand iQuick iRatio i(QR) iin i2017-2021 iis isaid ito ibe ivery igood. iThe iactivity iratios imeasured iusing iFixed iAssets iTurn iOver i(FATO) iand iTotal iAssets iTurn iOver i(TATO) iin i2017-2021 iare ivery ieffective.